Experimental and numerical study on flexural behavior of steel fiber reinforced high–strength concrete (SFRHC) beams - Shi Ke; Zhaohang Gao (Scientific Reports)
Abstract This study investigates the flexural behavior of steel fiber reinforced high-strength concrete (SFRHC) beams through experimental testing and numerical analysis. Eleven beams were subjected to four-point bending tests, with three primary variables: steel fiber volume fraction, beam depth, and longitudinal reinforcement ratio. The experimental program examined the load-midspan deflection relationships and failure modes throughout the loading process, and the results were validated through finite element analyses. Results demonstrated that increasing both the steel fiber volume fraction and beam depth led to enhanced cracking loads and ultimate loads. While the longitudinal reinforcement ratio significantly influenced the ultimate load capacity, its effect on the cracking load was minimal. Based on these findings, a new formula was developed to predict the flexural capacity of SFRHSC beams, incorporating the crack-bridging effect of steel fibers in the cracked section. The proposed formula showed excellent agreement with the experimental results.